Exploring smartphone usage patterns and perceived dependency: A cross-sectional study in Australia - Saqib Nawaz; Matthew Mitchell; Tanya Linden; Jahar Bhowmik (Acta Psychologica)
Smartphones have become indispensable in modern society, serving both everyday life and professional work. While they offer numerous advantages, their excessive use may cause adverse effects. Using a Uses and Gratifications Theory (UGT) framework, this descriptive cross-sectional study in Australia presents a comparative analysis of individual smartphone usage in relation to that of friends and family, alongside an examination of self-reported experiences of dependency related to smartphone use. A sample of 523 adults completed a self-report questionnaire assessing their smartphone usage, smartphone dependency, and the activities they frequently performed on their smartphones. The bivariate analysis conducted in this study revealed significant associations between self-reported smartphone use and various socio-demographic factors, including age, gender, parental status, and occupational status. Specifically, individuals aged 18–40, males, non-parents, and students reported higher levels of smartphone use compared to their respective counterparts. Regarding the most frequently performed smartphone activities, males and employed participants reported spending the majority of their time using social media and engaging in audio and video activities. The findings of this study also indicate that a significant portion of participants perceive their smartphone use as higher than that of their peers, reflecting a perceived compulsion to remain continuously connected and engaged. These findings show the influence of socio-demographic factors in understanding smartphone-related behaviours and highlight the need for targeted interventions and strategies addressing excessive smartphone use and dependency.